EMPIRICAL STUDY: PROFESSIONAL COMPETENCE, PEDAGOGIC COMPETENCE AND ACHIEVEMENT MOTIVATION ON TEACHER PERFORMANCE AT AL-WASHLIYAH VOCATIONAL SCHOOL MEDAN - Abd. Rasyid Syamsuri; Abd. Halim; Julianto Hutasuhut; Lukman Nasution (Jurnal Ekonomi, 2022)
The purpose of this study is to examine the effects of, professional competence, Pedagogic Competence and Achievement Motivation on the performance of the teachers at Al-Washliyah Private Vocational School Pasar Senen 2 in Medan. The population of this quantitative research is the 32 teachers of Al Washliyah Private Vocational School in Pasar Senen 2 Medan. Using saturation sampling is the sampling method. When every member of the population is used as a sample, it is known as a saturated sampling technique. 32 teachers work at the Al-Washliyah Private Vocational School in Pasar Senen 2 Medan, therefore all of them are the study's subjects. According to the study's findings, professional competence affects teacher performance in a positive and significant way. On teacher performance, pedagogical competence has a positive and significant impact. On teachers' performance, achievement motivation has a positive and significant impact. The performance of teachers at Al-Washliyah Private Vocational School Pasar Senen 2 Medan is simultaneously positively and significantly impacted by professional competence, pedagogic competence, and achievement motivation. Since the variables of professional competence, pedagogical competence, and achievement motivation had an Adjusted R2 value in this study of 0.816, they can account for 81.6% of teacher performance